Adolescent menstrual health: management and participation of the education and health sectors - Delgdo-Ordaz, Carlos Manuel; Becerril-Montekio, Víctor; Campero-Cuenca, Lourdes; Rodríguez-López, Andrea Guadalupe (Horizonte Sanitario, 2024)
Objective. To identify and analyze the elements and conditions of menstrual health management (information and education; health services and menstrual health management products) of public secondary schools and the participation of education and health sectors. Materials and methods. Mixed-concurrent study with female students, and education and health personnel. We applied a questionnaire to adolescents in three secondary schools to investigate about their experience regarding their management of menstrual periods. We made semistructured interviews with education and health personnel about their opinion regarding this issue and a focal group with students from one of the schools. We made a descriptive parametric analysis of the quantitative results and the qualitative results were analyzed using matrixes to identify relevant categories and codes. Results. A total of 117 students answered the questionnaire, out of which, 15 participated in the focal group. Four members of the education personnel and six of the health professionals answered the interviews. The main sources of information about menstruation were the students’ mothers and schools. The health personnel recognizes limitations to provide it. The students acknowledge absenteeism at school and problems related to the lack of products and conditions that favor menstrual health management. The education and health personnel consider that intersector collaboration would help solve important deficiencies. Conclusions. Menstrual health management not only depends on the joint action of the education and health sectors; it also requires the collaboration of other sectors of society to be able to respond to a multifaceted need. Key words: Reproductive health; adolescent health; menstruation; healthcare sector; Mexico.